Perjanjian Kerjasama pada Perusahaan Pertamina (Persero) Akibat Wanprestasi - I Wayan Eka Yasa; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Konstruksi Hukum, 2021)
The characteristic form of the SPBU entrepreneur's cooperation agreement with PT. Pertamina (Persero) is using a standard or standard agreement. The formulation of the problem is how the characteristics of the cooperation agreement at PT. Pertamina (Persero) with SPBU entrepreneurs, and the legal consequences of default in the cooperation agreement at PT. Pertamina (Persero). The research method uses normative legal research, with a problem approach using a statutory approach and a conceptual approach. The concept of a standard agreement in terms of form, in this research there is always a written agreement, the growth of which is now mostly achieved in a written form that uses standardized agreements, with the intention of taking concrete actions to save time, money and energy.If the implementation of the cooperation agreement between the SPBU entrepreneur and PT is violated, there will be legal consequences. Pertarnina (Persero) through non-litigation and litigation methods. Not confusing because it has been promulgated by Law no. 30 of 1999. the purpose of this study, among others, to determine the form of the characteristics of the cooperation agreement at PT. Pertamina (Persero) with SPBU entrepreneurs as well as knowing the legal consequences of default in the cooperation agreement at PT. Pertarnina (Persero).